Orthopedic Combination Pull Headgear with an Expanded Inner Bow for Class II Correction - Sharma, Tanmay; Kumar, Santosh; Naqvi, Zuber Ahamed; Jain, Ridam; Gupta, Bhaskar (Journal of Orofacial Research, 1970)
A successful orthodontic treatment depends upon proper diagnosis and treatment plan, as in this case combination pull headgear was use for correction of skeletal class II discrepancy.At the end of treatment an improvement in the facial profile was observed and skeletal as well as occlusal correction was achieved.